Intercropping with pear and cover crops as a strategy to boost soil carbon sequestration in the Taihang mountains’ fragile ecosystems - Zhang, Chi; Tong, Shanshan; Zhang, Ruifang; Li, Xuguang; Wang, Xin-Xin; Wang, Hong (Frontiers in Plant Science, 2025)
IntroductionSoil carbon sequestration capacity in ecologically fragile areas of the Taihang Mountains’ gneiss slopes demands immediate attention. This study evaluated the synergistic effects of land-use transition (from barren hills to cropland to pear orchards) and cover crop intercropping on soil carbon storage.MethodsField sampling and experiments were conducted at 72 sites in Fuping County. The analysis combined multi-index assessment of soil physicochemical properties with partial least squares structural equation modeling (PLS-SEM).ResultsLand-use transition significantly increased soil carbon storage. In 8-year-old pear orchards, the organic carbon storage in the 0-20 cm soil layer reached 26.08 tC/ha, representing a 151.89% increase compared to cultivated land (10.35 tC/ha). Meanwhile, soil carbon storage in the 20-40 cm layer increased by 83.97% to 13.58 tC/ha. Under the cover cropping pattern, ryegrass in the surface 0-20 cm soil of 8-year-old orchards showed an 18.5% improvement in efficiency over natural grass. In the 20-40 cm deep soil, winter rape increased organic carbon content by 22.43% to 10.59 g/kg.DiscussionThe synergistic mechanism was attributed to increased carbon input from cover crops and root systems, optimized soil physical structure (bulk density decreased by 5.1%-8.0%, porosity increased by 2.1%-4.1%), and formation of a nutrient-carbon pool synergy. Available potassium, phosphorus, and organic carbon were significantly positively correlated. This pear orchard and cover crop intercropping system exemplifies a practical Nature-based Solutions (NbS) pathway, achieving an annual carbon sink growth rate of 4.2-5.8 tC/(ha·a). Its core mechanism lies in constructing a triple synergy of “carbon sequestration enhancement, structural optimization, and nutrient cycling”, which enhances ecosystem services multidimensionally while fostering a resilient agricultural production system. This practice provides a technical paradigm for synergizing carbon neutrality goals and ecological restoration in fragile mountainous areas.